The Black Metropolis in the Twenty-First Century: Race, Power, and Politics of Place - Bullard, Robert D. (Rowman & Littlefield Publishers, 2007)
This book brings together key essays that seek to make visible and expand our understanding of the role of government (policies, programs, and investments) in shaping cities and metropolitan regions; the costs and consequences of uneven urban and regional growth patterns; suburban sprawl and public health, transportation, and economic development; and the enduring connection of place, space, and race in the era of increased globalization. Whether intended or unintended, many government policies (housing, transportation, land use, environmental, economic development, education, etc.) have aided and in some cases subsidized suburban sprawl, job flight, and spatial mismatch; concentrated urban poverty; and heightened racial and economic disparities. Written mostly by African American scholars, the book captures the dynamism of these meetings, describing the challenges facing cities, suburbs, and metropolitan regions as they seek to address continuing and emerging patterns of racial polarization in the twenty-first century. The book clearly shows that the United States entered the new millennium as one of the wealthiest and the most powerful nations on earth. Yet amid this prosperity, our nation is faced with some of the same challenges that confronted it at the beginning of the twentieth century, including rising inequality in income, wealth, and opportunity; economic restructuring; immigration pressures and ethnic tension; and a widening gap between 'haves' and 'have-nots.' Clearly, race matters. Place also matters. Where we live impacts the quality of our lives and chances for the 'good life.'